Medical Education Reform in China in the 21st Century: A Literature Review - Ling T; Shen Y; Zhang Y; Tang J; Zhao E (Advances in Medical Education and Practice, 2024)
Tianlong Ling,* Yuguang Shen,* Yuanruohan Zhang,* Jian Tang, Enhao Zhao Department of Gastrointestinal Surgery, Ren Ji Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Enhao Zhao; Jian Tang, Department of Gastrointestinal Surgery, Ren Ji Hospital, Shanghai Jiao Tong University School of Medicine, No. 1630 East Road, Shanghai, 200120, People’s Republic of China, Tel + 13818147043, Email microenhao@163.com; tkf28@163.comAbstract: Facing resource shortages and increasing gaps between regions and populations during the 20th century, around the 70s, the Chinese government authorized local governments to independently operate their own medical system, including medical education, to provide basic medical services and meet healthcare needs. These multiple independent but unparallel medical education systems throughout the nation inevitably created education quality disparities. Around the beginning of the 21st century, the Chinese government started a medical education standardization reform. This study aims to review and critically analyze these reform efforts toward standardization in medical schools and postgraduate and continuing education. All the background information, data, findings, government measures, etc. presented in this article were obtained through literature searches on PubMed, Baidu Scholar, and respective official online documents. Some of the key search criteria are, but not limited to, medical education reform in China and medical education history in China. These data were accessed in 2022. Standardization has been the core of reform in all three phases of medical education in China since the beginning of the 21st century. The three/five/eight principle, which refers to years of medical school, has been the backbone of medical school education in pursuing the “ 2030 healthy China” goal. The government streamlined postgraduate education further by establishing official licensing examination and launching a five+three+X model, which represents years required for medical school education, standardized residence, and specialty training, respectively. The standardization of continuing education is ongoing. Official and unified appraisal tests are in the pilot stage, whereas other areas have yet to change. Hopefully, this study will provide insight for future reform or research, or inform other countries.Keywords: medical education, reform, China, postgraduate, continuing education